The" Special Study": On the disintegration and reintegration of the contemporary city - Albrecht, Sven Michael (School of Architecture, Planning and Geomatics, 2021)
This Study is only an attempt at a brief' outline to a vast and complex problem. It does not endeavour to deal with the more specific problems of disintegrational forces in cities such as the population explosion, speculative and uncontrolled land exploitation and building, sprawling ribbon development and more specific reasons for central area decay. As the "Special Study" required by the thesis, it intends to describe the urban context for the envisaged Ethical Centre and thereby amplify the social context described in the “Research". It finally concludes the thoughts which led to the development and. concept of an Ethical· Centre.